ChemInform Abstract: Supported Gold Nanoparticles for Efficient α‐Oxygenation of Secondary and Tertiary Amines into Amides. Issue 43 (7th October 2016) - Jin, Xiongjie; Kataoka, Kengo; Yatabe, Takafumi; Yamaguchi, Kazuya; Mizuno, Noritaka
Abstract: An efficient heterogeneously Au/Al2 O3 ‐catalyzed α‐oxygenation of secondary and tertiary amines is developed using elemental oxygen as oxidant.